Interdisciplinary Action in Halls of EJA: the projects work in the light of focus-cultural history - Cyntia Graziella Guizelim Simões Girotto; Elieuza Aparecida de Lima (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This article aims to discuss the organization of work teaching in classrooms of Pejão (Program of Education for Youth and Adult - Unesp - Linda) through the Work Projects, which underlie actions from the perspective of interdisciplinary Theory History-Culture. Pointing to the pedagogical implications of this conception of education, considering the formation of educating young adults and forth the use of time and space for education, production of knowledge, the procedure to information given to school subjects, the development / implementation / development / evaluation of projects of interdisciplinary work in the light of the focus vygotiskiano. Therefore, our gaze is theoretical and methodological back-up for a particular context: the classes of its shares in EJA interdisciplinary. Discuss such issues as follows: the first section, we present the general theory, discussing key concepts such as mediation, activity, learning, development, and then inserted the actions of students and educators of EJA. In a second section, we draw some lessons of that theory, to (re) present and (re) thinking projects in the EJA, resignified and resizing them by vygotiskiano bias.